1985
DOI: 10.1128/aac.27.6.916
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical mechanisms of the antileishmanial activity of sodium stibogluconate

Abstract: Pentavalent antimonial agents such as sodium stibogluconate (Pentostam; Burroughs Welicome Co., London, United Kingdom) are the drugs of choice for the treatment of leishmaniasis, but their biochemical mechanisms of action are virtually unknown. The viability of Leishmania mexicana (WR 227) promastigotes and amastigotes was decreased 40 to 61% by a 4-h exposure to 500 ji.g of Sb (in the form of stibogluconate) per ml. Such exposure also resulted in a 51 to 65% decrease in incorporation of label into DNA, RNA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0
6

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(56 citation statements)
references
References 14 publications
3
47
0
6
Order By: Relevance
“…The actual survival of intracellular amastigotes encountered in the mammalian host determines disease pathogenesis. Importantly, promastigote and amastigote forms surviving in two disparate biological environments are very different in terms of metabolic pathways and their susceptibility to anti-leishmanial compounds (13,14). Therefore, observations with intracellular amastigotes addressing questions related to parasite survival are more relevant and could lay the foundation for rational strategies of drug development.…”
mentioning
confidence: 99%
“…The actual survival of intracellular amastigotes encountered in the mammalian host determines disease pathogenesis. Importantly, promastigote and amastigote forms surviving in two disparate biological environments are very different in terms of metabolic pathways and their susceptibility to anti-leishmanial compounds (13,14). Therefore, observations with intracellular amastigotes addressing questions related to parasite survival are more relevant and could lay the foundation for rational strategies of drug development.…”
mentioning
confidence: 99%
“…Se utilizaron concentraciones crecientes y graduales de antimonio (8,12,16,20,24,26,28,32, 33 mg/ml), hasta alcanzar una concentración final de 37 mg/ml. En un trabajo previo, para demostrar un comportamiento diferencial frente al medicamento entre la cepa susceptible y la resistente al antimonio pentavalente, se evaluó la resistencia in vivo infectando hámsters con las dos cepas y midiendo el tamaño de la nariz antes de la inoculación, después del desarrollo de la lesión (día 42), terminado el tratamiento con antimonio pentavalente (día 52) y cinco días después del tratamiento (día 57) (no se presentan los datos).…”
Section: Inducción De Resistencia In Vitrounclassified
“…Se han reportado varios blancos celulares para el antimonio pentavalente y el antimonio trivalente , incluyendo el tripanotión, que es el principal agente reductor de tioles en el parásito (20)(21)(22).…”
unclassified
“…Initial studies suggested that sodium stibogluconate [Sb(V)] inhibits macromolecular biosynthesis in amastigotes (18), possibly via perturbation of energy metabolism due to inhibition of glycolysis and fatty acid ␤-oxidation (16). However, the specific targets in these pathways have not been identified.…”
Section: Antimonialsmentioning
confidence: 99%